Deteksi Kematangan Buah Mangga secara Destruktif dan Non-Destruktif - Awit Mulyaningtyas; Gaida Zulfa Azzahra; Zahrotul Munawwaroh; Riana Listanti (Sekolah Vokasi, Universitas Sebelas Maret, 2025)
Mango (Mangifera indica L.) is a fruit rich in fiber, vitamin C and β-carotene. Mango production in Indonesia is quite high, but export value is still low due to various post-harvest problems. Maturity level is one of the keys in the mango trade, but it is difficult to maintain due to the climatic nature of the fruit. A grading process is required to separate mangoes with optimal ripeness levels until they reach consumers. Maturity level can be measured through various parameters, including physical and chemical attributes. There are two methods to determine the ripeness of mango fruit, destructive and non-destructive. The destructive method uses bay flower extract as a pH indicator. The non-destructive method uses double ring resonator technology, HSI color space transformation, and fruit position in water. The results show that the HSI color space transformation method is more recommended because it is simpler and more efficient.